Vulnerabilidade e autonomia de adolescentes e jovens do contexto rural em tratamento oncológico - Siqueira, Fernanda Duarte (2023)
This study aimed to understand the vulnerability of adolescents and young people in a rural context undergoing cancer treatment, to understand the process of autonomy of adolescents and young people in a rural context undergoing cancer treatment and to describe the social support network of adolescents and young people in a rural context undergoing cancer treatment. This is a qualitative, descriptive and exploratory research based on the health vulnerability framework of José Ricardo Ayres and the autonomy of Paulo Freire. The study setting was an oncology service at a university hospital in the southern region of Brazil. Adolescents aged 10 to 19 and young people aged up to 24 years old, who had experienced cancer, from rural areas, undergoing oncological treatment up to a maximum of five years before the start of data collection were included. Data were collected through semi-structured, individual and in-person interviews and construction of a genogram and ecomap with 15 adolescents and young people during the period from April 2021 to September 2022. The research was approved by the Ethics Committee under opinion: 4.594.079. The data was subjected to inductive thematic analysis. The results showed three thematic categories. Challenges of oncological treatment for adolescents and young people in rural contexts; Reframing the experience: ―I have cancer, but cancer doesn't have me‖ and (Re)building networks: family, friends, going through the same process and being cared for. And that led to the formulation of the thesis: adolescents and young people in rural contexts face unique challenges due to a combination of factors related to individual vulnerability, limited access to information about their health, diagnosis and treatment of cancer, resulting in lower awareness of their disease which, influenced by the stigma and culture of their rural community, makes it difficult to share information about cancer, which impacts on their autonomy. Social and programmatic vulnerability influenced, to a large extent, by geographic isolation. Adolescents and young people in rural areas have autonomy and take an active role in their own care and decision-making during cancer treatment. They become aware of their own reality and (re)build the social support network and agents of transformation in their own lives. There is an interconnection between vulnerability and autonomy, as overcoming vulnerability depends, to a large extent, on the exercise of autonomy. However, understanding individual, social and programmatic vulnerability makes it possible to promote the empowerment of adolescents and young people in rural contexts to face the challenges of cancer treatment. It is concluded that, despite the challenges of cancer treatment, not only related to the disease itself, but also social exclusion, the context in which they live, social stigma, the desire to overcome and the desire to live in search of autonomy persists. The implications for Nursing practice permeate the understanding of the experience of adolescents and young people from the rural context undergoing cancer treatment, taking into account the uniqueness of these individuals considering them in their entirety, the dimensions of the sociocultural context and the geographic space in which they live.